Rebalancing with India: safeguarding the Indo-Pacific maritime region - Bana, Sarosh (2016)
The Indian Navy’s foray into the Western Pacific is a demonstration of New Delhi’s Look East-Act East policy. It also responds to President Obama’s overture to India for a strategic partnership in balancing the rise of China.